PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WEBSITE BLOGGER PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL KELAS X UNTUK MENINGKATKAN MINAT BELAJAR SISWA [DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON BLOGGER WEBSITE FOR THE TOPIC OF SYSTEMS OF LINEAR EQUATIONS IN TWO VARIABLES IN GRADE X TO ENHANCE STUDENTS' LEARNING INTEREST] - Valentina, Febriyani; Setiawan, Rubono; Wiraya, Ario (JOHME: Journal of Holistic Mathematics Education, 2024)
In the era of Industry 4.0, the need for more attractive and interactive learning instruments has become increasingly evident, especially considering the declining interest in traditional lecture methods among students. The learning media developed in this study aims to leverage multimedia elements such as text, images, animations, and videos to enhance students' understanding and capture their attention towards abstract mathematical concepts. By utilizing the Blogger platform, this media provides flexible access for both teachers and students, offering a more active, enjoyable, and participatory learning experience. This research focuses on developing interactive learning media for Grade 10 students using a Blogger platform for the topic of Systems of Linear Equations in Two Variables. The learning media is designed to meet the criteria of validity, practicality, and effectiveness in enhancing students' learning interest, while also evaluating the levels of these criteria in the media. The Research and Development (R&D) approach was employed in this study, using the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research instruments included expert validation sheets, student and teacher response questionnaires, model feedback instruments, Pancasila profile instruments, and student learning interest instruments. The trial was conducted in Class X BDP, involving 41 students selected through purposive sampling. Validation results indicate that this learning media has a high level of validity, with an average score of 92.2% from material experts and 83.5% from media experts. The practicality of the media, based on student and teacher responses, model feedback, and the Pancasila profile, showed an average score of 3.4 (good) from students, 3.8 (very good) from teachers, 3.4 (good) from model feedback, and 3.3 (good) from the Pancasila profile. The learning media's effectiveness is evidenced by a 68% improvement in students' learning interest, categorizing it as moderately effective. The study concludes that the interactive learning media based on the Blogger platform for Grade 10 Systems of Linear Equations in Two Variables satisfies the criteria of being valid, practical, and effective for classroom use. Moreover, this media provides significant flexibility for teachers in designing and presenting learning materials, while also offering students the chance to learn independently and interactively. Therefore, this learning media not only enhances learning interest but also provides a comprehensive and holistic learning experience.BAHASA INDONESIA ABSTRACT: Di era teknologi 4.0, kebutuhan akan instrumen pembelajaran yang lebih atraktif dan interaktif menjadi semakin jelas, terutama mengingat metode ceramah tradisional yang semakin kurang diminati oleh siswa. Dengan menggunakan teks, gambar, animasi, dan video, penelitian ini berupaya untuk mengembangkan media pembelajaran untuk meningkatkan pemahaman siswa serta menarik perhatian mereka terhadap konsep-konsep matematika yang sering kali bersifat abstrak. Dengan menggunakan platform Blogger, media ini tidak hanya memberikan akses yang fleksibel bagi guru dan siswa, tetapi juga menawarkan pengalaman belajar yang lebih aktif, menyenangkan, dan partisipatif. Penelitian ini secara khusus difokuskan pada pengembangan media pembelajaran interaktif untuk siswa Kelas X, yang memanfaatkan situs website blogger pada materi Sistem Persamaan Linear Dua Variabel (SPLDV). Media ini dirancang agar memenuhi kriteria validitas, kepraktisan, dan efektivitas dalam meningkatkan minat belajar siswa, serta untuk mendeskripsikan tingkat kevalidan, kepraktisan, dan keefektifan media pembelajaran tersebut. Pendekatan Penelitian dan Pengembangan (R&D) digunakan dalam penelitian ini, dengan menerapkan model ADDIE yang mencakup tahap Analisis, Desain, Pengembangan, Implementasi, serta Evaluasi. Instrumen penelitian yang digunakan meliputi lembar validasi oleh ahli, angket respon siswa dan guru, instrumen feedback gelar model, profil Pancasila, serta instrumen minat belajar siswa. Uji coba dilakukan pada kelas X BDP dengan melibatkan 41 siswa yang dipilih melalui teknik purposive sampling. Hasil validasi menunjukkan bahwa media pembelajaran ini memiliki tingkat validitas yang tinggi dengan rata-rata skor 92,2% dari ahli materi dan 83,5% dari ahli media. Kepraktisan media, berdasarkan respon siswa dan guru, feedback gelar model, dan profil Pancasila, menunjukkan skor rata-rata 3,4 (baik) dari siswa, 3,8 (sangat baik) dari guru, 3,4 (baik) dari feedback gelar model, dan 3,3 (baik) dari profil Pancasila. Efektivitas media pembelajaran ini ditunjukkan dengan adanya peningkatan minat belajar siswa sebesar 68% (cukup efektif). Secara keseluruhan, penelitian ini menemukan bahwa media pembelajaran interaktif berbasis website blogger untuk materi SPLDV kelas X telah memenuhi kriteria sebagai alat yang valid, praktis, dan efektif dalam proses pembelajaran. Selain itu, pengajar memiliki keleluasaan yang signifikan dalam membuat dan menyampaikan konten pendidikan dengan media ini, serta libatkan diri dalam pembelajaran mandiri dan tingkatkan keterlibatan siswa. Dengan demikian, media pembelajaran ini tidak hanya meningkatkan minat belajar, tetapi juga memberikan pengalaman belajar yang komprehensif dan menyeluruh.